AN INSIGHT TO THE PHARMACOGNOSY OF SHATAVARI (ASPARAGUS RACEMOSUS WILLD.) - R.H, *Arya; V.V, Shincymol; Oommen, Sara Monsy (International Journal of Ayurveda and Pharma Research, 2018)
Asparagus racemosus Willd. (Shatavari) belonging to the family Asparagaceae is a drug well known since ages. It is regarded as the queen of herbs. Shatavari is not only a potent medicine but is also used as a vegetable in many parts of the world. The therapeutic applicability of the drug extends from aphrodisiac, galactogogue, diuretic, tonic, styptic, antibacterial, and antimycotic. Inthe Ayurvedic samhitas, there is repeated mentioning of the drug in the treatment aspects of Rakthapitta (bleeding disorders), Sthanyavardhaka (galactogogue), Rakshoghna of Vranitha and Soothika (antimicrobial activity), and in Mutrakrchracikitsa (urinary disorders). This work aims at understanding the organoleptic features, microscopic details and powder microscopy of the tuberous root powder of Shatavari (Asparagus racemosus Willd.). Even though the drug Shatavari is well known and used widely, detailed studies regarding the microscopic characters and the powder microscopy has not been documented in detail covering the entire aspects. In the light of authentic Pharmacopoeial texts, the cell constituents of the sample has been analysed and the powder microscopy also revealed the presence of calcium oxalate crystals, pitted vessels, tracheids etc, which also affirms the genuineness of the source drug Shatavari. Yet another concern is with the widespread use of adulterants. Shweta musali (Chlorophytum borivilianum L.) is used instead of Shatavari at many places knowingly or unknowingly. Hence a thorough understanding of the genuine drug in terms of its microscopic as well as powder character is very much essential to prevent the adulteration as well as providing a key to the identification of plant source.